5.7.12 Problems 1101 to 1200

Table 5.585: Solved using series method

#

ODE

Mathematica

Maple

7343

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

7344

\[ {}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0 \]

7345

\[ {}y^{\prime \prime }+\frac {y}{4 x} = 0 \]

7346

\[ {}x y^{\prime \prime }+y^{\prime }-x y = 0 \]

7687

\[ {}y^{\prime \prime }-x y^{\prime }+y = 0 \]

7688

\[ {}y^{\prime \prime }+3 x^{2} y^{\prime }-x y = 0 \]

7689

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

7690

\[ {}y^{\prime \prime }+x^{3} y^{\prime }+x^{2} y = 0 \]

7691

\[ {}y^{\prime \prime }+y = 0 \]

7692

\[ {}y^{\prime \prime }+\left (x -1\right )^{2} y^{\prime }-\left (x -1\right ) y = 0 \]

7693

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+y = 0 \]

7694

\[ {}y^{\prime \prime }+y \,{\mathrm e}^{x} = 0 \]

7696

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+\alpha \left (\alpha +1\right ) y = 0 \]

7708

\[ {}x^{2} y^{\prime \prime }+\left (x^{2}+x \right ) y^{\prime }-y = 0 \]

7709

\[ {}3 x^{2} y^{\prime \prime }+x^{6} y^{\prime }+2 x y = 0 \]

7710

\[ {}x^{2} y^{\prime \prime }-5 y^{\prime }+3 x^{2} y = 0 \]

7711

\[ {}x y^{\prime \prime }+4 y = 0 \]

7712

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

7713

\[ {}\left (x^{2}+x -2\right )^{2} y^{\prime \prime }+3 \left (x +2\right ) y^{\prime }+\left (x -1\right ) y = 0 \]

7714

\[ {}x^{2} y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 0 \]

7715

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

7716

\[ {}4 x^{2} y^{\prime \prime }+\left (4 x^{4}-5 x \right ) y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

7717

\[ {}x^{2} y^{\prime \prime }+\left (-3 x^{2}+x \right ) y^{\prime }+y \,{\mathrm e}^{x} = 0 \]

7718

\[ {}3 x^{2} y^{\prime \prime }+5 x y^{\prime }+3 x y = 0 \]

7719

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+x^{2} y = 0 \]

7720

\[ {}x^{2} y^{\prime \prime }+x \,{\mathrm e}^{x} y^{\prime }+y = 0 \]

7721

\[ {}2 x^{2} y^{\prime \prime }+\left (x^{2}+5 x \right ) y^{\prime }+\left (x^{2}-2\right ) y = 0 \]

7722

\[ {}4 x^{2} y^{\prime \prime }-4 x \,{\mathrm e}^{x} y^{\prime }+3 y \cos \left (x \right ) = 0 \]

7723

\[ {}x^{2} \left (-x^{2}+1\right ) y^{\prime \prime }+3 \left (x^{2}+x \right ) y^{\prime }+y = 0 \]

7724

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (1+x \right ) y = 0 \]

7725

\[ {}x^{2} y^{\prime \prime }+2 x^{2} y^{\prime }-2 y = 0 \]

7726

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+\left (-x^{3}+3\right ) y = 0 \]

7727

\[ {}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+2 \left (1+x \right ) y = 0 \]

7728

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

7729

\[ {}x^{2} y^{\prime \prime }-2 x^{2} y^{\prime }+\left (4 x -2\right ) y = 0 \]

7730

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

8072

\[ {}y^{\prime } = 2 x y \]

8074

\[ {}y^{\prime }+y = 1 \]

8076

\[ {}y^{\prime }-y = 2 \]

8078

\[ {}y^{\prime }+y = 0 \]

8080

\[ {}y^{\prime }-y = 0 \]

8082

\[ {}y^{\prime }-y = x^{2} \]

8084

\[ {}x y^{\prime } = y \]

8086

\[ {}x^{2} y^{\prime } = y \]

8088

\[ {}y^{\prime }-\frac {y}{x} = x^{2} \]

8091

\[ {}y^{\prime } = \frac {1}{\sqrt {-x^{2}+1}} \]

8092

\[ {}y^{\prime } = 1+y \]

8093

\[ {}y^{\prime } = x -y \]

8095

\[ {}y^{\prime \prime }+x y^{\prime }+y = 0 \]

8096

\[ {}y^{\prime \prime }-y^{\prime }+x y = 0 \]

8097

\[ {}y^{\prime \prime }+2 x y^{\prime }-y = x \]

8098

\[ {}y^{\prime \prime }+y^{\prime }-x^{2} y = 1 \]

8099

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }+y = 0 \]

8100

\[ {}y^{\prime \prime }+\left (1+x \right ) y^{\prime }-y = 0 \]

8101

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

8102

\[ {}y^{\prime \prime }+x y^{\prime }+y = 0 \]

8103

\[ {}y^{\prime \prime }+y^{\prime }-x y = 0 \]

8104

\[ {}y^{\prime \prime }+y^{\prime }-x y = 0 \]

8105

\[ {}y^{\prime \prime }+\left (p +\frac {1}{2}-\frac {x^{2}}{4}\right ) y = 0 \]

8106

\[ {}y^{\prime \prime }+x y = 0 \]

8107

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+p^{2} y = 0 \]

8108

\[ {}y^{\prime \prime }-2 x y^{\prime }+2 p y = 0 \]

8109

\[ {}x^{3} \left (x -1\right ) y^{\prime \prime }-2 \left (x -1\right ) y^{\prime }+3 x y = 0 \]

8110

\[ {}x^{2} \left (x^{2}-1\right ) y^{\prime \prime }-x \left (1-x \right ) y^{\prime }+2 y = 0 \]

8111

\[ {}x^{2} y^{\prime \prime }+\left (2-x \right ) y^{\prime } = 0 \]

8112

\[ {}\left (1+3 x \right ) x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+2 y = 0 \]

8113

\[ {}y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8114

\[ {}x y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8115

\[ {}x^{2} y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8116

\[ {}x^{3} y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8117

\[ {}x^{4} y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

8118

\[ {}x^{3} y^{\prime \prime }+\left (-1+\cos \left (2 x \right )\right ) y^{\prime }+2 x y = 0 \]

8119

\[ {}4 x^{2} y^{\prime \prime }+\left (2 x^{4}-5 x \right ) y^{\prime }+\left (3 x^{2}+2\right ) y = 0 \]

8120

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+4 x y = 0 \]

8121

\[ {}x^{3} y^{\prime \prime }-4 x^{2} y^{\prime }+3 x y = 0 \]

8122

\[ {}4 x y^{\prime \prime }+3 y^{\prime }+y = 0 \]

8123

\[ {}2 x y^{\prime \prime }+\left (3-x \right ) y^{\prime }-y = 0 \]

8124

\[ {}2 x y^{\prime \prime }+\left (1+x \right ) y^{\prime }+3 y = 0 \]

8125

\[ {}2 x^{2} y^{\prime \prime }+x y^{\prime }-\left (1+x \right ) y = 0 \]

8126

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+x^{2} y = 0 \]

8127

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x^{2}}-\frac {y}{x^{3}} = 0 \]

8128

\[ {}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0 \]

8129

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+\left (4 x +4\right ) y = 0 \]

8130

\[ {}4 x^{2} y^{\prime \prime }-8 x^{2} y^{\prime }+\left (4 x^{2}+1\right ) y = 0 \]

8131

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

8132

\[ {}x^{2} y^{\prime \prime }-x^{2} y^{\prime }+\left (x^{2}-2\right ) y = 0 \]

8133

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0 \]

8134

\[ {}\left (x -1\right )^{2} y^{\prime \prime }-3 \left (x -1\right ) y^{\prime }+2 y = 0 \]

8135

\[ {}3 \left (1+x \right )^{2} y^{\prime \prime }-\left (1+x \right ) y^{\prime }-y = 0 \]

8136

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

8137

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8138

\[ {}x \left (1-x \right ) y^{\prime \prime }+\left (\frac {3}{2}-2 x \right ) y^{\prime }+2 y = 0 \]

8139

\[ {}\left (2 x^{2}+2 x \right ) y^{\prime \prime }+\left (1+5 x \right ) y^{\prime }+y = 0 \]

8140

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+\left (5 x +4\right ) y^{\prime }+4 y = 0 \]

8141

\[ {}\left (x^{2}-x -6\right ) y^{\prime \prime }+\left (3 x +5\right ) y^{\prime }+y = 0 \]

8142

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+p^{2} y = 0 \]

8143

\[ {}\left (1-{\mathrm e}^{x}\right ) y^{\prime \prime }+\frac {y^{\prime }}{2}+y \,{\mathrm e}^{x} = 0 \]

8144

\[ {}y^{\prime \prime }+2 x y = x^{2} \]

8145

\[ {}y^{\prime \prime }-x y^{\prime }+y = x \]

8146

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{3}-x \]